Carbon sequestration and soil nitrogen enrichment in Robinia pseudoacacia L. post-mining restoration plantations - Xanthopoulos, Giorgos; Radoglou, Kalliopi; Derrien, Delphine; Spyroglou, Gavriil; Angeli, Nicolas; Tsioni, Georgia; Fotelli, Mariangela N. (Frontiers in Forests and Global Change, 2023)
Robinia pseudoacacia L. (black locust) has been extensively used for restoring degraded lands, following anthropogenic interventions like coal mining. Here we have addressed the contribution of black locust restoration plantations, established on overburden post-mining material, to carbon storage and to soil nitrogen enrichment at the largest lignite center in Greece. Carbon stocks and fluxes in all pools of the ecosystem, as well as the foliar nitrogen resorption efficiency and soil N stocks were quantified and the effect of plantations’ age was tested. The young age of the plantations (4–24 years) resulted in a relatively low total ecosystem C stock (56.7 t ha−1), which was partitioned among the different pools in the following order: above-ground biomass (50%) > black locust-derived SOC (24%) > coarse roots (14%) > deadwood (6%) > forest floor (5%) > fine roots (less than 1%). Litterfall started early in the growing season and together with fine roots that had a turnover rate of 0.62 yr−1, fueled soil organic carbon. SOC accrual, referring to the accumulation of SOC derived by black locust, declined with age. However, further SOC accumulation is expected, based on the potential SOC storage capacity of soil at the area. C stocks in above- and below-ground biomass increased linearly with age. The same response was observed for soil N stock and NRE, indicating that despite the N2-fixing capacity of black locust, there was still a poor pedospheric N supply and a need for efficient N cycling. Overall, the studied restoration plantations have a considerable contribution to C and N accumulation at the degraded post-mining sites. These positive effects are expected to further increase at least until the plantations reach maturity.